Gravity wave and microphysical effects on bow echo development - Selin, Rebecca Denise Adams, author; Johnson, Richard, advisor; van den Heever, Susan, committee member; Bienkiewicz, Bogusz, committee member; Schumacher, Russ, committee member (Colorado State University. Libraries, 2012)
Numerical simulations of the 13 March 2003 bow echo over Oklahoma are used to evaluate bow echo development and its relationship with gravity wave generation and microphysical heating profile variations. The first part of the research is directed at an explanation of recent observations of surface pressure surges ahead of convective lines prior to the bowing process. Multiple fast-moving n = 1 gravity waves are generated in association with fluctuations in the first vertical mode of heating in the convective line. The surface impacts of four such waves are observed in Oklahoma mesonet data during this case. A slower gravity wave is also produced in the simulation, which is responsible for the pre-bowing pressure surge in the model. This gravity wave is generated by an increase in low-level microphysical cooling associated with an increase in rear-to-front flow and low-level downdrafts shortly before bowing. The wave moves ahead of the convective line and is manifested at the surface by a positive pressure surge ahead of the convective line. The low-level upward vertical motion associated with this wave, in conjunction with higher-frequency gravity waves generated by the multicellularity of the convective line, increases the immediate pre-system CAPE by approximately 250 J kg-1. Two-dimensional heating profiles from this idealized, full-physics bow echo simulation are placed as a constant heat source in another simulation without moisture, to evaluate what type of gravity waves are produced by a heating profile from a given instance in time. A one-dimensional vertical mean heating profile is calculated from each two-dimensional profile, and a statistical method is used to evaluate the significance of each vertical mode. A number of gravity waves are produced in the dry simulation despite their vertical mode lacking statistical significance in the one-dimensional profile, suggesting that horizontal variations in the heating profile are important to consider. Microphysical sensitivity tests further elucidate the importance of the horizontal distribution of the microphysical heating profile. The tests used variations in the graupel parameter to evaluate its effect on bowing development and related forecasting parameters. Idealized and case study simulations showed that simulations using a larger, heavier, more "hail-like" graupel parameter with faster fallspeeds have decreased evaporation and melting rates concentrated closer behind the convective line, compared to simulations with a smaller, slower-falling, more "graupel-like" graupel parameter. This resulted in increased precipitation efficiency but a smaller stratiform region, weaker cold pool, weaker downdrafts and surface wind gusts, rear-to-front flow that remained elevated until close behind the convective line, and delayed bowing development in the "hail-like" simulations. Output from the case study sensitivity tests were compared to data from the Oklahoma Mesonet, which showed "hail-like" microphysical variations can cause significant variations in simulated forecasting parameters, including a 90 minute delay in onset of bowing, 150% weaker surface wind gusts, and a 600% increase in storm-total precipitation. Results from this work emphasize the importance of microphysical heating and cooling profiles in development of bow echoes, be it through the generation of multiple gravity waves and their feedback to the convection, or through direct modification of convective features such as the rear-inflow circulation and the cold pool strength. The pressure surge gravity wave generated by low-level cooling prior to bowing, and associated destabilization of the environment immediately in advance of the system, improves understanding of the cause of convective intensification as the system bows. However, the strong connection shown between bow echo development and microphysical processes, and the highly diverse nature of microphysical parameterizations, presents a challenge to the prediction of these severe weather phenomena.
Keywords: microphysics; mesoscale meteorology; severe storms; convection; gravity waves